Non-ribosomal Peptide Synthetase Gene Clusters in the Human Pathogenic Fungus Scedosporium apiospermum - Le Govic, Yohann; Papon, Nicolas; Le Gal, Solène; Bouchara, Jean-Philippe; Vandeputte, Patrick (Frontiers in Microbiology, 2019)
Scedosporium species are opportunistic fungi which preferentially affect patients with underlying conditions such as immunosuppression or cystic fibrosis (CF). While being the second most common molds capable to chronically colonize the CF lungs, the natural history of infection remains unclear. In filamentous fungi, a broad range of important secondary metabolites that are recognized as virulence factors are produced by multidomain non-ribosomal peptide synthetases (NRPSs). The aim of this study was to provide a global in silico analysis of NRPS-encoding genes based on the recently sequenced Scedosporium apiospermum genome. We uncovered a total of nine NRPS genes, of which six exhibited sufficient similarity scores with other fungal NRPSs to predict the class of the generated peptide: siderophores (n = 2), epidithiodioxopiperazines (n = 2), and cyclopeptides (n = 2). Phylogenetic trees based on the multiple alignments of adenylation (A) domain sequences corroborated these findings. Nevertheless, substrate prediction methods for NRPS A-domains tended to fail, thus questioning about the exact nature of the peptide produced. Further studies should be undertaken since NRPSs, which are not synthesized by human cells, could represent attractive therapeutic targets.